5
$\begingroup$

This is a snapshot of Baby Rudin:

Theorem For every real $x>0$ and every integer $n>0$ there is one and only one positive real $y$ such that $y^n=x$.

This number $y$ is written $\sqrt[n]{x}$ or $x^{1/n}$.

Proof That there is at most one such $y$ is clear, since $0<y_1<y_2$ implies $y_1^n<y_2^n$.

Let $E$ be the set consisting of all positive real numbers $t$ such that $t^n<x$.

If $t=\frac{x}{1+x}$ then $0\le t<1$. Hence $t^n\le t<x$. Thus $t\in E$, and $E$ is not empty.

If $t>1+x$ then $t^n\ge t>x$, so that $t\notin E$. Thus $1+x$ is an upper bound of $E$.

Hence Theorem 1.19 implies the existence of

$$y=\sup E$$

To prove that $y^n=x$ we will show that each of the inequalities $y^n<x$ and $y^n>x$ leads to a contradiction.

The identity $b^n-a^n=(b-a)(b^{n-1}+b^{n-2}a+\cdots+a^{n-1})$ yields the inequality

$$b^n-a^n<(b-a)nb^{n-1}$$

when $0<a<b$.

Assume $y^n<x$. Choose $h$ so that $0<h<1$ and

$$h<\frac{x-y^n}{n(y+1)^{n-1}}$$

Put $a=y,b=y+h$. Then

$$(y+h)^n-y^n<hn(y+h)^{n-1}<hn(y+1)^{n-1}<x-y^n$$

Thus $(y+h)^n<x$, and $y+h\in E$. Since $y+h>y$, this contradicts the fact that $y$ is an upper bound of $E$.

Assume $y^n>x$. Put

$$k=\frac{y^n-x}{ny^{n-1}}$$

Then $0<k<y$. If $t\ge y-k$, we conclude that

$$y^n-t^n\le y^n-(y-k)^n<kny^{n-1}=y^n-x$$

Thus $t^n>x$, and $t\notin E$. If follows that $y-k$ is an upper bound of $E$.

To get the definition of $h$, I understand we need $x-y^n$ in the denominator to make the whole thing greater than $0$, but where does the denominator $n(y+1)^{n-1}$ come from?

The same question on the form of $k$. Why do we need such a denominator $ny^{n-1}$?

$\endgroup$
2
  • $\begingroup$ Would you like to see an alternative proof ? $\endgroup$ Jun 10, 2018 at 3:32
  • $\begingroup$ @DanielWainfleet If your proof is simpler than Rudin's :) $\endgroup$ Jun 10, 2018 at 14:32

4 Answers 4

9
$\begingroup$

Rudin follows the mathematical style of writing his 'probe for the proof' on a piece of scrap paper, and upon arriving at the solution, writing up a formal and terse proof that hides the 'mathematical eyebrow sweat' that went behind it.

The $\text{1.21 Theorem}$ the OP is analyzing comes right after Rudin introduces the real numbers as a complete ordered field in Chapter 1; the solution there can only use the developed axiomatic machinery.

Let us probe this matter and work up some 'sweat'.

We have our fixed positive real number $x$ and an integer $n \gt 0$. In general the only easy thing is to find a real number $a \gt 0$ such that

$\tag 1 a^n \lt x$

Can we do better? Can we 'make $a$ larger' so that $\text{(1)}$ still holds?

Suppose $b \gt a$. How do we 'enforce' the condition that $b^n \lt x$?

$\tag 2 [ b^n \lt x ] \text{ iff } [ (b^n - a^n + a^n) \lt x ] \text{ iff } [ (b^n - a^n) \lt (x - a^n) ]$

It may take you a page or two of scrap paper to discover that the key to solving this is that

$\tag 3 b^n-a^n<(b-a)nb^{n-1}$

is always true with $0 \lt a \lt b$. So by setting up some bound $M$ and with $b = a + h$, you can write

$\tag 4 b^n \lt h M + a^n \lt hM + x$

Geometrically, Rudin knows that $E$ is an interval. The set $F$ of real positive numbers $u^n \gt x$ is also an open interval. The supremum of $E$ is equal to the infimum of $F$.

The above describes the conceptual thinking behind Rudin's proof (no calculus allowed).


The following theory gets the result in a different manner, and proposition 2 clarifies part of Rudin's argument in his proof construction.

Let $x$ be some fixed positive real number and $n \in {\mathbb Z}^+$.

Proposition 1: Let $D \subset (0, +\infty)$ be a nonempty set of real numbers and assume that for any $d \in D$, $d^n \gt x$. Then $[\text{inf(D)}]^n \ge x$.
Proof
Let $y = \text{inf(D)}$ and to arrive at a contradiction, assume that $y^n \lt x$. Choose $h$ so that $0<h<1$ and

$\quad h<\frac{x-y^n}{n(y+1)^{n-1}}$

Set $a=y$ and $b=y+h$. Then, using Rudin's (3) from the prior section,

$\quad (y+h)^n-y^n<hn(y+h)^{n-1}<hn(y+1)^{n-1}<x-y^n$

But then $(y+h)^n<x$ and so $y + h$ must be a lower bound for $D$. Yet it is greater than $y$ which is the $\text{glb}$, a contradiction. $\blacksquare$

Proposition 2: Let $D \subset (0, +\infty)$ be a nonempty set of real numbers and assume that for any $d \in D$, $d^n \lt x$. Then $[\text{sup(D)}]^n \le x$.
Proof
Let $y = \text{sup(D)}$ and to arrive at a contradiction, assume that $y^n \gt x$. Set

$\quad h=\frac{y^n-x}{ny^{n-1}}$

It is easy to see that $0 \lt h \lt y$.

Set $a=y-h$ and $b=y$. Then, using Rudin's (3) from the prior section,

$\quad y^n-(y-h)^n<hny^{n-1}= y^n-x$

But then $(y-h)^n>x$ and so $y - h$ must be an upper bound for $D$. Yet it is smaller than $y$ which is the $\text{lub}$, a contradiction. $\blacksquare$

Let $E = \{t \gt 0 \, | \, t^n \lt x \}$ and $F = \{t \gt 0 \, | \, t^n \gt x \}$.

Proposition 3: $\text{sup(E)} = \text{inf(F)}$ and if we denote this number by $\gamma$, then $\gamma^n = x$.
Proof
Let $\beta = \text{inf(F)}$. By proposition 1, $\beta^n \ge x$.
Let $\alpha = \text{sup(E)}$. By proposition 2, $\alpha^n \le x$.
Since $\beta$ is an upper bound for $E$, $\alpha \ge \beta$.
Since $\alpha$ is an lower bound for $F$, $\alpha \le \beta$.
So $\alpha = \beta$ and the proposition follows. $\blacksquare$


In a comment the OP had a question on how to derive the inequality. To be complete, even if it is no longer necessary, consider this:

The identity $b^n-a^n=(b-a)(b^{n-1}+b^{n-2}a+\cdots+a^{n-1})$ yields the inequality

$b^n-a^n<(b-a)nb^{n-1}$

when $0<a<b$.

We have $n$ terms in $b^{n-1}+b^{n-2}a+\cdots+b^0 a^{n-1}$, but since $a \lt b$,

$|b^{n-1}a^0+b^{n-2}a^1+\cdots+b^0 a^{n-1}| \lt |b^{n-1}a^0|+|b^{n-2}a^1|+\cdots+|b^0 a^{n-1}| \lt$
$\quad |b^{n-1}|+|b^{n-1}|+\cdots+|b^{n-1}| \lt n b^{n-1}$


In his question, the OP ask where does the denominator come from in

$\quad h<\frac{x-y^n}{n(y+1)^{n-1}}$

This is the same thing as working with an $[\varepsilon , \delta]$ proof in calculus. After the 'probing', we set $h$ (like we do with $\delta$) to what works and shows that we can control the quantities. In essence, we are using the fact that the function $f(x) = x^n$ is continuous, but the book still hasn't discussed that concept.

$\endgroup$
3
  • $\begingroup$ +1 for noting the hidden "mathematical eyebrow sweat." Any proof of a nontrivial theorem in Rudin hides all intuition, which is why trying to prove a theorem yourself, or intuitively explaining the proof to yourself, can be useful. $\endgroup$
    – Robert D-B
    Jun 10, 2018 at 18:09
  • $\begingroup$ Could you just give me a hint on how to derive $b^n - a^n<(b-a)nb^{n-1}$ from $b^n - a^n < x- a^n$? I do not have a clue. $\endgroup$ Jun 10, 2018 at 18:50
  • 1
    $\begingroup$ @ChunjingGU Yea, I didn't want to prove this but I will try to work out some more details. $\endgroup$ Jun 10, 2018 at 19:32
3
$\begingroup$

In a comment I offered to give a different proof. The proposer accepted, on condition that it is simpler. Whether this is simpler, or not, is not for me to say.

Let $x>0$ and $n\in \Bbb Z^+.$ We show $\exists y\in \Bbb R^+\;(y^n=x).$

Lemma 1. For any $n\in \Bbb N$ we have $\forall r>0\;\exists s>0\;(\;1+r>(1+s)^n\;).$

Proof: Let $0<s<2^{-n}\min (1,r)).$ (For example let $s=2^{-n-1}\min (1,r)$.) For $1\leq j\leq n$ we have $0<\binom {n}{j}s^j\leq \binom {n}{j}s.$ So we have $(1+s)^n=$ $1+\sum_{j=1}^n\binom {n}{j}s^j\leq$ $ 1+\sum_{j=1}^n\binom {n}{j}s=$ $1+(2^n-1)s<$ $1+(2^n-1)2^{-n}r<1+r.$

Corollary 1 . If $y>0$ and $y^n>x$ then $\exists q\in \Bbb Q^+\cap (0,y)\;(q^n>x).$

Proof: Let $y^n=x(1+r).$ By Lemma 1 let $s>0$ such that $1+r>(1+s)^n.$ Let $q\in \Bbb Q^+\cap (y/(1+s),y).$ Then $1<(1+r)(1+s)^{-n}<1+r.$ So we have $x<x(1+r)(1+s)^{-n}=y^n(1+s)^{-n}=(y/(1+s))^n<q^n.$

Lemma 2. If $y>0$ and $y^n<x$ then $\exists q\in \Bbb Q \cap (y,\infty)\;(q^n<x).$

Proof: Let $y'=1/y.$ Let $x'=1/x.$ Let $(y')^n=(x')^{-1}(1+r).$ By Corollary 1 there exists $q'\in \Bbb Q \cap (0,y')\;( (q')^n>x').$ Now let $q=1/q'.$

Part 3. By the construction of $\Bbb R$ by Dedekind cuts on $\Bbb Q,$ if $A,B$ are non-empty subsets of $\Bbb Q$ such that $A\cup B=\Bbb Q$ and such that $\forall a\in A\;\forall b\in B\;(a<b)$ then there is a unique $y\in \Bbb R$ such that $y=\sup A=\inf B.$

Let $A=(\Bbb Q\cap (-\infty,0])\cup \{q\in \Bbb Q^+: q^n<x\}.$ Let $B=\{q\in \Bbb Q^+: q^n\geq x\}.$ Let $y=\sup A=\inf B.$

We have $y>0$ because if $q\in (0, \min (1,x)\cap \Bbb Q$ then $q^n\leq q<x$ so $q\in A$ so $y=\sup A\geq q>0.$

If $y^n>x$ then by Corollary 1, $\exists q\in Q^+\cap (0,y)\;(q^n>x),$ contrary to $y=\inf B.$

If $y^n<x$ then by Lemma 2, $\exists q\in \Bbb Q^+\cap (y,\infty)\;(q^n<x),$ contrary to $y=\sup A.$

Therefore $y^n=x.$ QED.

NOTES: Since $\Bbb Q$ is order-dense (in itself) (i.e. there is a rational strictly between any 2 rationals), it follows by the construction of $\Bbb R$ from $\Bbb Q$ by Dedekind cuts that there is a rational strictly between any 2 reals, which was used to obtain $q$ in the proof of Corollary 1, and also in Part 3 to show that $y>0$. We also used, throughout, that $\forall a,b>0\;\forall n\in \Bbb Z^+\;(a<b\iff a^n<b^n).$ In Part 3 we have $B\ne \emptyset$ because (again by the construction of $\Bbb R$ ) $\exists q\in \Bbb Z^+ \;(q>\max (1,x))$ so $q^n\geq q>x$ so $q\in B.$

$\endgroup$
6
  • $\begingroup$ Note that in later editions Rudin relegates the explicit construction of the real numbers to the appendix, using an axiomatic approach. See notendur.hi.is/vae11/%C3%9Eekking/… $\endgroup$ Jun 11, 2018 at 0:38
  • $\begingroup$ @CopyPasteIt. I have not read this book. Not to criticize it, nevertheless I would say that you will need $some$ def'n of $\Bbb R$ to prove anything about it $\endgroup$ Jun 11, 2018 at 1:01
  • $\begingroup$ fyi: Rudin: 1.19 Theorem: There exists an ordered field $\mathbb R$ which has the least upper bound property. Moreover, $\mathbb R$ contains $\mathbb Q$ as a subfield. - those are the axiomatic ingredients. $\endgroup$ Jun 11, 2018 at 1:14
  • $\begingroup$ Which analysis book do you use, if any? $\endgroup$ Jun 11, 2018 at 2:00
  • 1
    $\begingroup$ FYI: I gave another partial answer that is a Rudin-Synthesis of your argument here; it is a direct brute force approach. $\endgroup$ Jun 12, 2018 at 14:39
1
$\begingroup$

The $n(y+1)^{n-1}$ is an arbitrary inclusion carefully crafted to cancel out the denominator in the inequality $\ldots hn(y+1)^{n-1} < \frac{x-y^n}{n(y+1)^{n-1}}n(y+1)^{n-1}=x-y^n$. Like you said, since $x-y^n > 0$, $h$ is still between 0 and 1, even when we add the new restriction.

Same goes for $k$.

$\endgroup$
0
$\begingroup$

As DanielWainfleet shows, you are well on you way if you can show that when $y^n \lt x$ you can find an $s \gt 0$ such that ${(y+s)}^n \lt x$. Also, the rest of his argument can be rewritten using only Rudin's axiomatic definition of $\mathbb R$ (no reason to mention Dedekind cuts).

Proposition: Let $x \gt 0$ and $n$ a positive integer. Suppose $y \gt 0$ and $y^n \lt x$. Then there exists a positive real number $s$ such that ${(y+s)}^n \lt x$.
Proof
We have

$\tag 1 {(y+s)}^n =y^n+\sum_{j=1}^n\binom {n}{j}y^{n-j}s^j$

Let $M = max[\,\binom {n}{j}y^{n-j}\,]_{ \, 1 \le j \le n}$ so that

$\tag 2 {(y+s)}^n \lt y^n+\sum_{j=1}^nMs^j$

We can now set $s = min(\frac{1}{2}, \frac{x - y^n}{2nM})$ so that

$\tag 3 {(y+s)}^n \lt y^n+\sum_{j=1}^nMs^j \lt y^n+\sum_{j=1}^nMs = y^n+ n M s \le y^n + \frac{x-y^n}{2} $

ensuring that ${(y+s)}^n \lt x$. $\blacksquare$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.